Religious agenda in Russian mainstream media: trends and controversies - Khroul Victor (Studia Humanitatis, 2024)
The lack of understanding by journalists of the religious life complexity and sensitivity, the difference between profane and sacred leads to dysfunctions in the reporting on religions. Content analysis of the most popular Russian mainstream media discovered the marginalization of texts about religion in the general information agenda of Russian mass media, with the dominance of Orthodox Christianity in journalistic texts and the underexposure of religious minorities, while the popular presentation of doctrinal matters remains in media minimal. In addition, a “crisis of experts” in publications on religious topics has been detected: journalists prefer to seek comments from officials and public activists more often than from religious scholars. The “conflict of formats” in media and religions, the mismatch of mutual perceptions of the boundaries of permissible and acceptable in the secular media and religious communities remains an important characteristic of the current state of media-religion relations in Russia.